Diversidades convergentes: subsídios para modelo de sistema de informação em incubadoras artístico-culturais a partir de estudo comparado entre Brasil e Canadá - Nisio Antonio Teixeira Ferreira (2008)
This work investigated cultural and artistical incubators by a comparative study of the field between Brazil and Canada, including the characteristics of this process in two incubators: Gênesis (Rio De Janeiro /RJ, Brazil) and Montréal Arts Interculturels (MAI - Montreal/QC, Canada). What it is an artistical and cultural incubator, what are theircharacteristics in the two countries and the establishment of a modelization of an artistical and cultural information system from this contraposition constitutes important issues of this work. Due to his initial stage, the research object demanded a panoramic approach through his theorical review, around three axles. First, culture as a symbolic good, carrying values and identity, but here as a product of the shockbetween rational and intuitive forces that could be institutionalized in a so-called art world and also in the evolution of information systems toward this area. Secondly, the possibility of configuration of culture as an informational good, that shocks but also transforms itself from and in the Information Society toward the economy of learning. Third, the culture as an economic good that has economical characteristics in the works of art, divided between those which are unique, such as visual andperforming arts, and those which are reproducible, such as the cultural industries of books, records and movies, and also in he public subventions to the sector. The work also includes the multilateral politics of the culture, especially the Cultural Diversity, one of the points of intersection and approach between Brazil and Canada, which aredistinguished through the cultural politics trajectory of each country and, in the Canadian case, with an emphasis in the trajectory of Quebec. This comparison brought two experiences of an artistical and cultural incubators in each country, and, once allied to the premises of chapters, resulted in the enumeration of a series of subsidies or categorizations to be considered for a modelization of an artistical and cultural information system for incubators in this field, as well as suggestions of future works, like a faceted work of the artistic occupation in Brazil, institutional indicators of culture and the flow and information needs of the incubated companies in an artistical and cultural incubation, amongst others.